Functional Use of Case Suffix +lA in Dialects of Giresun Province and its Region - Aydoğdu, Özkan (Fırat University, 2023)
The aim of this study is to designate the functional use of case suffix +lA in dialects of Giresun and its region and the role of each function in the syntax. In the functional approach, the case is determined not according to the suffixes the noun takes, but according to the tasks which it is assigned in the sentence. The +lA case suffix examples used in our study were determined by scanning the work called Giresun İli ve Yöresi Ağızları prepared by Demir and Aydoğdu (2009). All the examples in which the detected +lA suffix is used have been evaluated by Daşdemir (2015) on the basis of the case categories created according to the functions and tasks in the syntax in accordance with the functional approach. As a result of the study, the outcome that the case suffix +lA is used in 7 different functions was reached. According to the frequency of usage, these functions are as follows: the instrumental case, commutative case, qualitative case, reciprocal case, genitive case, causative case and locative of time case. The tasks they undertake in these functions are determined as case adverb, instrumental object, reciprocity object, commutative object, genitive object, case object, cause object, time object and designation/qualifying adjective.

Bu çalışmanın amacı, Giresun ili ve yöresi ağızlarında +lA hâl ekinin işlevsel kullanımını ve her bir işlevin söz dizimi içerisindeki görevini tespit etmektir. İşlevsel yaklaşımda hâl, ismin aldığı eklere göre değil cümlede üstlenmiş olduğu işleve göre belirlenmektedir. Çalışmamızda kullanılan +lA hâl eki örnekleri, Demir ve Aydoğdu (2009) tarafından hazırlanan “Giresun İli ve Yöresi Ağızları” adlı eser taranarak tespit edilmiştir. Tespit edilen +lA hâl ekinin kullanıldığı bütün örnekler de Daşdemir (2015) tarafından işlevsel yaklaşıma uygun olarak ekin söz dizimi içerisindeki işlev ve görevlerine göre oluşturulan hâl kategorileri esas alınarak değerlendirilmiştir. Çalışmanın sonucunda, +lA hâl ekinin 7 farklı işlevde kullanıldığı tespit edilmiş olup bu işlevler, kullanım sıklığına göre; vasıta hâli, beraberlik hâli, niteleme hâli, karşılıklılık hâli, ilgi hâli, sebep hâli ve zamanda bulunma hâli şeklinde sıralanmıştır. Bahsi geçen işlevlerin söz diziminde yüklendikleri görevler ise hâl zarfı, vasıta tümleci, karşılıklılık tümleci, beraberlik tümleci, ilgi tümleci, hâl tümleci, sebep tümleci, zaman tümleci ve belirtme/niteleme sıfatıdır.
GİRESUN İLİ VE YÖRESİ AĞIZLARINDA +lA HÂL EKİNİN İŞLEVSEL KULLANIMI
Keywords: Language Studies (Other); Dil Çalışmaları (Diğer)